049 Sonographic tendon abnormalities can predict symptomatic tendinopathy in marathon runners. (3rd March 2020) - Eby, Sarah; Teramoto, Masaru; Zurbuchen, Rudi; Cummings, Keith; English, Joy; Cushman, Daniel M
Abstract : Background: Tendinopathies of the patellar and Achilles tendons are common injuries among athletes and the general population. These injuries are costly, time-intensive to treat, and significantly limit activity. Predicting and eventually preventing these injuries is invaluable. Objective: Evaluate the relationship between sonographic tendon abnormalities and development of future injury in community marathon runners. Design: Prospective longitudinal cohort study. A blinded reviewer rated pre-race ultrasound images for tendon abnormalities, including thickening, hypoechogenicity, intratendinous delamination, or calcifications. Setting: 2019 Salt Lake City Marathon Participants: Marathon or half-marathon runners with no knee or ankle symptoms. 166 were screened; 138 completed the study (36.2±12.0 years of age, male: n =68). Assessment of risk factors: Ultrasound evaluation of bilateral Achilles and patellar tendons immediately prior to the race and longitudinal surveys of subsequent injury development immediately following the race, and 1 and 3 months post-race. Main outcome measurements: Patellar or Achilles injury development. Statistical analyses included calculating relative risk (RR) with a 95% confidence interval (CI) and hazard ratio (HR) with a 95% CI from the Cox proportional hazards (PH) model. Results: Sonographic abnormalities were found among 12.3% (left Achilles) and 26.8% (right patellar) of runners. Runners with sonographic abnormalities were 2 times (RR=2.20, 95% CI=1.15, 4.22, p =0.040) more likely to develop pain in the Achilles tendon within three months compared to those with normal ultrasounds. The Cox PH model indicated that sonographic abnormalities were associated with 2 times (HR=2.35, 95% CI=1.10, 4.99, p =0.027) higher risk of developing post-race pain in the Achilles tendon after adjusting for runners' demographics and training regimens. No significant findings were observed between sonographic abnormality and post-race pain in the patellar tendon for the current observation period. Conclusions: Pre-race sonographic Achilles tendon abnormalities are associated with development of Achilles tendon pain within 3 months. Subsequent injury development, including at 6, 9, and 12-months post-race is pending.